(untitled) (Applied Biological Research, 2014)
The present study was aimed to investigate the time intervals required by the eggs of two ascarid species - Baylisascaris transfuga retrieved from Melursus ursinus (Sloth bear), and Toxascaris leonina, retrieved from Panthera leo persica (Asiatic/Indian lion) to reach infective stages at controlled temperature (27±1°C) in 0.4% formalin solution as well as in faecal samples as such. The incubated material revealed that the eggs advanced to two-cell stage at day 2 and 3 post-incubation in case of T. leonina and B. transfuga, respectively, in formalin solution as well as in faecal samples. The final infective stages having 2nd stage larvae inside the eggs were observed at day 12 and 9 post incubation in 0.4% formalin solution and at day 14 and 9 post-incubation in faecal samples in case of B. transfuga and T. leonina, respectively. To check the reoccurrence of infection of these parasites having direct life cycle, better management practices involving anthelmintic therapy of the infected individu